THE EFFECT OF FINANCIAL MANAGEMENT PRACTICES ON PROFITABILITY IN IDX-LISTED COMPANIES - Adel Adel; Endah Sri Wahyuni; Elvi Nilda; Samsul Bahry Harahap; Bustami Bustami (Journal Dialectica (Journal of Accounting Research), 2026)
Research Objectives: To analyze the effect of cash management, inventory management, and cost management on the profitability of companies listed on the Indonesia Stock Exchange (IDX).​ Design/ Methodology / Approach Research: A quantitative research design with a causal-associative approach. The study utilized secondary data from corporate financial statements. Data analysis was performed using multiple linear regression, preceded by classical assumption tests (normality, multicollinearity, and heteroskedasticity) with SPSS software. Research Results: The analysis revealed that partially, the variables of cash management, inventory management, and cost management do not have a significant effect on profitability. The simultaneous test (F-test) also indicated that these three variables jointly do not significantly affect profitability. The low coefficient of determination (R²) indicates the model has limited explanatory power.​ Implications of Research Results: The profitability of the studied companies is likely influenced by other factors beyond the model, such as investment strategies, capital structure, operational efficiency, and market conditions. Companies are advised not to focus solely on managing cash, inventory, and costs but to also consider other strategic factors to enhance profitability.